A simple measure to study multinational income inequality - Gharehgozli Orkideh; Atal Vidya (Review of Economic Perspectives, 2021)
Using the Big Mac Index, we offer a simple measure to study the real income inequality. We provide a multidimensional real income inequality analysis by exploring the Coefficient of Variation and the Big Mac Affordability of households across all income deciles of 28 countries for the years 2000 to 2013. We look more into a few of the most interesting countries in our analysis in order to have explanations for the wide range of income inequality we observe. We compare Denmark and Mexico as representatives of the 'more equal' and 'less equal' countries in our analysis, and we find a visible difference in the share of each decile to the top decile of income between the two countries. However, we observe that, although a more equal country, Denmark has been exp eriencing a rise in income inequality while a less equal country (Mexico) has been experiencing a reduction in income inequality. We also focus on the United States and study how it compares to Russia, a country that shows a different direction of income inequality compared to the U.S.A. We find that while the wage income inequality in Russia has been correlated inversely with its growth, in the U.S.A., the overall growth and wage income inequality have been positively correlated.
Keywords: D31; O57; 330; Big Mac Index; Income Inequality; Income Distribution Decile; Comparative Country Studies